VELOCITY DISTRIBUTION IN PIPE CROSS-SECTION UNDER LAMINAR FLOW CONDITIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the formation and importance of velocity profiles in drilling-fluid circulation as a key factor affecting hydraulic efficiency, pressure losses, and cuttings transport during drilling operations. Focus is given to the development of laminar and transitional flow regimes within the drill pipe and annular space, the impacts of viscosity and density, and the evolution of the flow profile near the bit entry. The analysis emphasises how velocity distribution influences the predictability of pressure gradients, the stability of cuttings suspension, and the risk of turbulence-induced erosion. Understanding these hydrodynamic principles allows drilling engineers to optimise pump performance, maintain safe flow regimes, and prevent sedimentation. The findings demonstrate that velocity-profile analysis provides a critical foundation for enhancing drilling efficiency, borehole stability, and overall operational safety.